Effects of Eucalyptus Camaldulensis Exracts on Trichimonas vaginalis Growth In vitro - A Kazemian; H YousofiDarani; N Zebardast; M Sereshti; Banaian S Banaian S; F Safdari; M Delaram; HA Yousofi; M Rafieian (Institue of Medicinal Plants, ACECR, 2012)
Background: Trichimonas vaginalis is a flagellate protozoa that cause trichomoniasis. Metronidazole which is drug of choice for treatment of this infection has many side effects so the patients are unsatisfied with its using, so it is necessary to seek for alternative drugs. Eucalyptus camaldulensis herb with strong anti-microbial affects is considered as an alternative drug.   Objectives: Investigating the effect of Eucalyptus camaldulensis as an alternative drug Trichomonas vaginalis in vitro.   Methods: Eucalyptus camaldulensis extraction was prepared using perculasion method. In test tubes containing parasite culture medium different concentrations of the plant extract were added. In other test tubes metronidazole or extract solvent as controls were added. 100 live Trichomonas vaginalis added to each tube and all tubes kept in 37ºC and tested for presence of the parasite every 24 hours up to 72 hours. For this purpose 10 microliter of each tube examined under microscope.   Results: in tubes with higher concentration of Eucalyptus camaldulensis extract and also in tube containing metronidazole no parasite was observed. In negative control tubes parasite had a normal growth. Conclusion: According to results of this study Eucalyptus camaldulensis extract had strong effects on Trichomonas vaginalis growth. Further investigation is recommended to use this plant as alternative drug for treatment of trichomoniasis.